Evaluasi alokasi Tempat Pembuangan Sampah Sementara (TPSS) di Kecamatan Denpasar Selatan dengan aplikasi GIS - Rohmah, Siti Ainur; Asmiwyati, I Gst. A. Ayu Rai; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p01, 2020)
One of sub-district in Denpasar that still faces garbage problems is South Denpasar which is due to its high population. The population of South Denpasar is 286,060 people. Based on the data obtained, each individual can dispose up to 0.004 m³ garbage each day. This the volume of waste in the population of South Denpasar Sub-district each day is 1,144.24 m³. However, the amount of waste has not been accommodated well within the number of existing landfills. This study aim is to determine the location of landfill in South Denpasar District. The variables used to determine the suitability of the landfill location are the road to the location, the distance of landfill to the river, land use, land availability and regional boundaries. The number of was determine by points in South Denpasar, amount of waste each day, number of existing population, perceptions and preferences of the people of South Denpasar. The analysis of landfill location was run by using a geographic information system (GIS). This research uses survey methods and data collection with an active approach of activities carried out on the site. The results of the analysis showed that there were 11 landfills recommendations. The location of these recommendations is in the immediate area of reach, which is within 1-2 km.